APPLICATION OF INSTRUMENTATION AND CONTROL SYSTEM FOR BIOGAS POWER GENERATION COMMISSIONING AT PTPN V KAMPAR PALM OIL MILL - Arya Bhaskara Adiprabowo; Bambang Muharto; Hana Nabila Anindita; Nur Azimah Salehah; Dwi Husodo Prasetyo; Semuel Pati Senda; Muhamad Rodhi Supriyadi; Nesha Adeliaa; Bayu Samodra (BRIN, 2020)
Biogas Power Plant (PLT) from palm oil mill effluent had been commissioned by a team from the Center of Technology for the Energy Resources and Chemical Industry, Agency for the Assessment and Application of Technology (PTSEIK-BPPT). The biogas power plant is located in PTPN V Kampar, Riau Province. A PLC (Programmable Logic Controller) has been implemented to support the operation of biogas power plant. Proper sensor selection has been done for each measurement applications. A computer and mimic panel is used as an interface for the operation of PLC. The master control system communicates with the slave control systems and Human Machine Interface (HMI) by means of ethernet communication protocol. Commissioning phase is carried out for 2 hours with a load of 450 kW. Instrumentation and control system is able to measure important variables such as fluctuation in methane numbers, pressures, and biogas flow rate to check the suitability of biogas supply in accordance to gas engine specification.